1989
DOI: 10.1148/radiology.172.2.2748830
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism after hip or knee replacement: postoperative changes on pulmonary scintigrams in asymptomatic patients.

Abstract: Serial pulmonary imaging has proved to be effective in the evaluation of patients undergoing total joint arthroplasty. A clinical dilemma arises in asymptomatic patients whose postoperative pulmonary images differ from the preoperative images. The authors prospectively evaluated 403 patients with serial imaging to determine the significance of changed postoperative images in asymptomatic patients undergoing total hip or knee arthroplasty. Twenty-two (5.5%) patients had significant changes on postoperative imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…25,26 Our data also show the importance of preoperative perfusion lung images in patients with lung surgery or lung related surgical procedures. A similar risk of developing pulmonary embolism should also be expected in postoperative patients who were operated on other organs.…”
Section: Discussionsupporting
confidence: 57%
“…25,26 Our data also show the importance of preoperative perfusion lung images in patients with lung surgery or lung related surgical procedures. A similar risk of developing pulmonary embolism should also be expected in postoperative patients who were operated on other organs.…”
Section: Discussionsupporting
confidence: 57%
“…[33][34][35] However, these authors also observed that about one in six patients have an abnormal lung scan after total knee or total hip surgery. Therefore, a lung scan may not be a useful screening test.…”
Section: Discussionmentioning
confidence: 97%
“…However, as these studies employed only plannar images, and were based on correlative findings with pulmonary angiography, which has a low sensitivity [7], different or modified approaches that can effectively diagnose PE are needed, especially for patients with elective surgery. The usefulness of preoperative and postoperative lung scintigraphy has been demonstrated in orthopedic surgery [16,17,20,21]. Detection of additional defects postoperatively is a key for the diagnosis of PE, and asymptomatic PE is a common event in postarthroplasty patients.…”
Section: Discussionmentioning
confidence: 99%
“…All segmental defects were detected postoperatively and comparison with baseline scan was not needed, demonstrating that postoperative SPECT is sufficient for screening postoperative PE in this study setting. In studies using planar images, detection of differences between pre-and postoperative scans was useful because of its low spatial resolution and low specificity [16,17,19]. In contrast, SPECT imaging has a higher specificity [12], allows segmental localization of the perfusion defect, and reveals additional defects not seen on planar scans [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation